COMMUNICATION STRATEGY FOR THE DEVELOPMENT OF ALMOUS ECOTURISM IN THE ISLAND OF THE KELAPA ISLAND - Muslim, Muslim (UNIVERSITAS PAKUAN, 2021)
This study aims to explore the perceptions of the community and tourists on the development plan for the marine alms ecotourism in the island of kelapa, and to formulate a communication strategy policy for the development of ecotourism in the Kelapa Island village. The approach used is a combination of communicative and qualitative approaches. Data analysis was compiled using tabulation, then interpreted descriptively qualitatively in accordance with the research objectives. The communication strategy implementation plan is carried out through a SWOT analysis. The perception of the village community to participate in its management so as to increase business opportunities and income. In addition, it can preserve rituals as a habitual action (hereditary action) and also contain transcendental values while maintaining natural preservation. The perception of visitors to the existence of sea alms strongly supports the ritual of